Prevalence of Stress, Anxiety and Depression among Intern Doctors during Hospital Ward Rotations: A Multicentre Experience from Bangladesh (Mugda Medical College Journal, 2026)
Stress is a common response to demanding situations and can adversely affect emotional, physical, and cognitive functioning. Intern doctors working in different medical college hospitals are particularly vulnerable due to heavy workloads, night duties and continuous exposure to critically ill patients. In Bangladesh, an extremely low doctor–patient ratio and overcrowded public hospitals further intensify their burden. A cross-sectional, descriptive study was conducted, between September 2024 and August 2025, to assess psychological distress among 118 purposively selected intern doctors from four government medical college hospitals in Dhaka city, Bangladesh. We used a pre-tested, structured questionnaire for data collection. Level of stress was measured using Kessler 10 Psychological Distress (K10), while anxiety level was determined using the General Anxiety Disorder 7 (GAD 7) scale and depression level by using Patient Health Questionnaire 9 (PHQ-9). The mean age of the participants was 25.3±0.83 years; most of the participants belonged to the 25–26 years age group. Male-female ratio was 1:1.5. The prevalence of stress, anxiety, and depression were found high at 68%, 76%, and 77% respectively. Logistic regression analysis showed that female and unmarried interns had markedly higher odds of stress (OR=26.6), while high workload increased anxiety risk (OR=6.11). Severe sleep disturbance strongly predicted all three conditions. Interns in the 9–12-month duration group had significantly higher odds of depression (OR=21.7). Overall findings highlight substantial psychological distress among intern doctors, closely linked to gender, workload, sleep quality, workplace stress, and internship duration. Improved working conditions and targeted mental health support are urgently needed to protect wellbeing of the intern doctors working at different medical college hospitals across the country.Mugda Med Coll J. 2026; 9(1): 59-66